Perencanaan Dan Perancangan Perpustakaan Harapan Indah Dengan Konsep Green Architecture Dengan Penekanan Pada Efisiensi Dan Konservasi Energi - Retno Fitri Astuti; Shilvie Shilvie; Purnama Sakhrial Pradini (Prosiding Sains dan Teknologi, 2022)
Indonesia’s growing energy needs have not been matched by an adequate energy supply. Efforts to support the earth’s sustainability require energy efficiency and conservation. Energy efficiency and conservation is an effort to save energy in buildings and in the landscape. To ensure long-term sustainability, current infrastructure such as hotels, apartments, housing and libraries must adopt and maintain these energy saving principles. Harapan Indah is a housing complex located in Bekasi City, Medan Satria Sub-District. Many schools and universities in Harapan Indah need a place for their students to do non-formal learning activities; thus, there is a growing need for a public library that accommodate groups within the community sustainably. The prospective library design will be guided by principles of energy efficiency and conservation, employing several technologies such as the use of solar panels, roof gardens technology, garden reduction, optimal lighting and natural ventilation. Keyword : Green Architecture, Sustainability, Energy Efficiency and Conservation, Library